Empowerment of Village-Owned Enterprises in Mallenreng Beach Tourism Management - Andi Serlina; Makmur; Nurhaliza; Muhammad Amar; Mochamad Nurdin (Masterpiece, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in stimulating local economic development through the management of village-based potential resources, particularly in the tourism sector. Panaikang Village, located in Sinjai Timur District, South Sulawesi, possesses significant coastal tourism potential, notably Mallenreng Beach. However, limited managerial capacity and inadequate understanding of tourism management have constrained the optimal performance of BUMDes in managing this destination. This community empowerment program aimed to strengthen the managerial capacity of BUMDes and local communities in managing Mallenreng Beach as a sustainable village tourism destination. The program was implemented through a participatory approach involving initial field surveys, problem identification, socialization, and capacity-building training activities conducted by the Student Organization Capacity Strengthening Program (PPK Ormawa) in collaboration with community service students. The activities focused on tourism management principles, destination branding, community involvement, and sustainable development strategies. The results indicate improved awareness and understanding among BUMDes managers and community members regarding tourism governance, resource utilization, and the importance of integrated management practices. Furthermore, the program contributed to the formulation of a tourism development concept emphasizing the sunrise attraction of Mallenreng Beach and supported the village’s participation in the 2023 National Tourism Village Competition. This empowerment initiative demonstrates that strengthening institutional capacity and community participation can enhance the competitiveness of village tourism, stimulate local economic growth, and support the achievement of sustainable development goals. Continuous mentoring and collaboration with higher education institutions are recommended to ensure long-term sustainability.